IMF Survey, Volume 35, Issue 19. (IMF Survey; IMF Survey ;, 2006)
John Lipsky on IMF role; Liberia; Middle East outlook; Country briefs: Chile, Iceland; Ukraine reforms; Syria's oil crunch; Measuring sovereign risk; Maastricht inflation criterion; financial sector supervision; IMF bookstore; Nouriel Roubini.